Human rights for the stateless: A case study of the Rohingya in Malaysia / Suganthy Sathasivam - Suganthy, Sathasivam (2015)
This paper focuses on the human rights violations against the Muslim minority, the Rohingya, an ancient ethnic group from the northern Rakhine in West Myanmar. Although they have been habiting Rakhine since the eight century, after Burma's independence in January 1948, friction began between the Burmese government and the Rohingya. It culminated when the Rohingya were not listed as citizens in the Citizenship Act of Burma 1982. Overnight, they were rendered stateless. This study is important as they suffer grave abuse of human rights in Malaysia as a result of their statelessness. Malaysia is not a party to the 1954 Convention Relating to the Status of Stateless Persons or the 1951 Convention Relating to the Status ofRefugees. Under Malaysian law they are illegal immigrants, whereby they are equated to economic migrants. They are detained under the Immigration Act 1959/63 (which has been since been amended in 1997 and 2000) as violating immigration laws for entering Malaysian borders without proper documentation and are held in immigration detention camps. Here and outside the detention centers there have been many reports of human rights abuse suffered by the Rohingya. The research approach adopted involves both quantitative and qualitative. It documents interviews with the Rohingya that have been undertaken by non-governmental organisations such Human Rights Watch and the United High Commissioner for Refugees. It reports on the current laws, practices and policies of the Immigration department that are harmful and discriminatory. Their dire conditions require an urgent solution, whereby recommendations for the Malaysian and Burmese government and other players in the international human rights arena have been put forth.